PENGARUH TOUCH TERHADAP PEMBELIAN KONSUMEN PADA RETAIL - Yovan Budiyanto (Universitas Trunojoyo Madura, 2016)
Retail business competition in Indonesia is growing very rapidly, and there was intense competition among retailers. Data showed that the numbers of retailers growth high 2012.It’s because, retailers become a good distribution channel for company, because consumers can quickly get the goods from the company, through retailers. Various ways used by retailers to win the competition, and have a superior sales figures than the competitors. One of the way is by applying experiential marketing,especially touch in retail store. Display product that allows consumers to interact with products, will lead to a positive impact on sales of products in the retailer. Consumers can obtain detailed information about it, such as weight, texture and characteristics. Even touch can affect the positive feelings of consumers to make purchases in the retail store, the application of good touch will be profitable for retailers. The conclusion of this conceptual article will show the effect of touch on consumer purchases made at retail stores according to some research results